Structure and socio-economic culture of Peasant Community in Perú (Revista Innova Educación, 2020)
ABSTRACT. Objective. Was to evaluate the organizational structure in peasant communities in Perú and their contribution to national economic development. It worked with 6 communities. Methods: Descriptive, observational. as instruments were: interview, survey, document review and the application of economic factors. Results: The economic factors are low, with enough solvency to get into debt.  Inability to strengthen the community. The agriculture production without markets, isolated sales. The present community model does not help to the new vision of community - business.     Conclusions: To work as community is not profitable, So, they are unable to given back money to members; The training has direct impact on community development and management skills. The liberalization of the land is dangerous because the peasants can end landless and poorest. The members are not interested to maintain the sustainability of the community. The contribution and payment the tax the peasants are exempt, they are affected by indirect tax such as IVA. It`s imperative to produce crops with greater demands at national and foreign market and it should be profitable too in a new community structure.
Keywords: Business development; peasant organization; profit; decision making